Using Patient‐Reported Outcomes in Two Program Examples Measuring Health Status in Primary Care: An Observational Study - Allison L. Soprovich; Hilary Short; Al‐Bakir Ali; Krista Brower; Arto Ohinmaa; Jeffrey A. Johnson (Health Science Reports)
ABSTRACT Background and Aims Patient‐reported outcome measures (PROMs) are increasingly used in primary care practices; however, the broad characteristics of this population pose unique challenges. Generic PROMs (e.g., EQ‐5D‐5L) measure general health status from the patient's perspective, contributing towards a comprehensive evaluation of health programming. This study describes the integration of the EQ‐5D‐5L within program evaluation in primary care in Alberta, Canada, using two program examples. Methods A retrospective, longitudinal, observational design was used. The Edmonton O‐day'min Primary Care Network (EOPCN) routinely collects the EQ‐5D‐5L in their exercise and active living and nutrition programs. Data collected between January 1, 2021 and March 31, 2022 was analyzed descriptively, by dimension, index, and visual analog scale (VAS) scores. Minimally important differences were used to interpret index (0.04) and VAS scores (7.0) and the Pareto Classification of Health Change was applied to the dimensions. Effect size of change in index and VAS scores and population comparisons were examined. Results In the exercise and active living program (n = 301), 72% were female with a mean age of 57 (±16) years, and 90.2% reported any problems (levels 2–5) in pain/discomfort. The mean index and VAS scores were 0.74 (±0.18) and 66.5 (±18.9), respectively. Among those with repeated measurement (n = 112), the greatest improvement was in usual activities (17%); the greatest deterioration was in pain/discomfort (25%). In the nutrition program (n = 573), 71% were female with a mean age of 50 (±17) years, and 75.9% reported any problems in pain/discomfort. The mean index and VAS scores were 0.77 (±0.19) and 70.1 (±15.6), respectively. Among those with repeated measurement (n = 212), the greatest improvement was in anxiety/depression (16%); the greatest deterioration was in pain/discomfort (26%). In both, health status was lower than the general Alberta population norms. No baseline characteristics were found to be statistically significant. Conclusion These results inform future programming, to help patient needs.